Penerapan Prinsip Good Governance dalam Sistem Informasi Aset Daerah di Badan Perencanaan Pembangunan Riset dan Inovasi Daerah Kota Probolinggo - Yasmin Eka Febrianti; Rosyidatuzzahro Anisykurlillah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Badan Perencanaan Pembangunan Riset dan Inovasi Daerah Probolinggo City utilizes the Regional Asset Information Sistem (SIASAD) to record and report Regional Property (BMD) in real time. However, there is a discrepancy between the percentage of Regional Government Financial Reports (LKPD) that comply with regulations, which is 100%, and the percentage of BMD data validity, which fluctuates between 86.21% in 2021 and 82.14% in 2024, indicating that the system is not optimal and there is inconsistency in BMD data. This study aims to evaluate the implementation of SIASAD in BMD management at BAPPERIDA Probolinggo City, based on the principles of Good Governance. The research method applied is qualitative with a case study approach involving data collection techniques such as interviews, observations, and document studies. The results of the study reveal that SIASAD supports the application of Good Governance through the principles of participation, consensus orientation, accountability, transparency, responsiveness, effectiveness and efficiency, fairness and inclusiveness, and compliance with the law. From this study, it can be concluded that the implementation of SIASAD contributes significantly to transparent and accountable BMD governance in accordance with the principles of Good Governance, although improvements are still needed in terms of public accessibility.